Factors That Limit Effective Administrative Behaviors of School Principals: A Mixed Method Study - Cansoy, Ramazan; Kutlu, Hayriye; Araşkal, Seçil; Bozkurt, Emine; Danışmaz, Nurmelek (Journal of History Culture and Art Research, 2018)
In this study, effective administrative behaviors that school principals exhibit according to teacher perceptions, their ineffective behavioral patterns, and their ineffective behavioral reasons were investigated. The study was conducted based on the mixed method. The explanatory design in which first quantitative data and then qualitative data are collected to explain quantitative data was conducted. A total of 200 teachers who could be reached from teachers employed in elementary, secondary and high schools located in Karabük province constituted the sample of the study. The participants in the qualitative section of the study were 19 teachers from different school types. Quantitative data were collected by the Administrative Effectiveness Scale. A semi-structured interview was used to obtain qualitative data. In this study, quantitative research findings showed that effective administrative behaviors of school principals were at the moderate level. According to these findings, it was observed that school principals’ behaviors in the areas such as supporting teacher professional development, sparing time to improve education and training, and well running of the reward system were not at sufficient levels. The findings in the qualitative section of the study supported these findings. In this context, qualitative findings conducted with teachers revealed that school principals’ administrative efforts to improve education and training in the school were not at the desired level. On the other hand, the fact that school administrators had shortcomings with respect to exhibiting behaviors for supporting teachers’ professional development, rewarding teacher achievements, well structuring of the incentive system and developing the relationship between school and environment was intensely stated by the participants. The fact that school principals were mainly focused on daily routines in the school rather than education and training activities, spared too much time to improve the physical conditions of the school and intensely spent time for official works and operations was found to be the reasons for them.